Examining Teachers’ Perspectives on the New Changes to the Promotion System of the Department of Education: Basis for Career Path Orientation Program - Osman, Arvie Joy; Adanza, Lito (JPAIR Multidisciplinary Research, 2024)
Effective promotion systems recognize and reward teachers’ dedication, incentivizing professional development and career progression. This study investigated the experiences and understanding of public elementary teachers in selected divisions in Region XII, Philippines, regarding the previous and new changes to the Department of Education’s promotion system. An explanatory sequential mixed-methods approach was used, combining quantitative surveys followed by qualitative interviews. Findings revealed that teachers generally understand both systems, emphasizing performance rating, experience, and education. Improvement areas include a clearer assessment of potential and more training in the previous system, while the new system needs smoother implementation and needs to address concerns about workload and transparency. Qualitative analysis identified key themes related to teacher experiences such as promotion types, criteria, self-directed learning, and equity and concerns regarding the new changes such as understanding, system acceptance, workload, and transparency. This study underscores the importance of addressing teachers’ understanding and experiences when implementing changes. Effective communication and clear information are crucial for morale and development. A well-designed promotion system prioritizing meritocracy, equity, and teacher well-being can enhance the teaching force and elevate education standards in Region XII. The research provides insights for DepEd policymakers to refine the promotion system and develop a Career Path Orientation Program (CPOP) responsive to teachers’ needs and aspirations.